(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The agroforestry system combines the best features of agricultural practices and forest ecosystems. This approach provides diverse environmental and socio-economic benefits, such as preventing soil erosion and degradation, increasing soil moisture and water retention, and yielding harvests from planted fruit trees, bushes, edible plants, and various agricultural crops. Additionally, agroforestry offers several added benefits, including enhanced biodiversity, beekeeping and improved pollination, carbon sequestration, and climate change mitigation and adaptation. With these advantages in mind, a 3.5 ha model agroforest was established in 2022 on the Southern bank of Lake Sevan, near the village of Tsovinar in the Martuni consolidated community. Over two years of project implementation, all major activities and system-forming elements were put in place, including fencing, an irrigation system, and the planting of approximately 10 000 tree and bush species, along with edible plants. This model, through further monitoring and evaluation, could provide strong justification for the Government of Armenia to expand its forest cover in alignment with its international commitments under the 2015 Paris Climate Agreement.